Return on Indian equities, 1980-99: the sensex portfolio - Gupta, L.C.; Choudhury, Utpal K. (2000)
This study examines the long-term rates of return on a representative portfolio of 30 Indian companies of the BSE Sensex over 1980-99. It compares the rate of return over various holding periods and decomposes it into capital appreciation and dividend. The study finds that the only lasting effect on equity portfolio returns is that of growth in earnings per share, which latter have been growing since 1990 as a result of liberalisation. - Reproduced
Keywords: Financial markets - India; Financial markets